The Role of Entrepreneurial Orientation and Product Innovation in Improving the Performance of Furniture SMEs - Khalifah, Risti Nur; Supriadi, Didit; Maulani, Galih Abdul Fatah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This study is intended to examine the Influence of Entrepreneurial Orientation and Product Innovation on the Performance of Furniture SME Businesses in Garut Regency. The purpose of this study is to determine the description and Influence of Entrepreneurial Orientation and Product Innovation on the Performance of SME Businesses in Garut Regency. The research method used is a quantitative approach method with data collection through questionnaires distributed directly and online using Google Forms then processed using SPSS for Windows version 25. The sample of this study consisted of 93 respondents who were Furniture SME actors in Garut Regency. The results of the analysis show that Entrepreneurial Orientation has an effect on the Performance of Furniture SME Businesses in Garut Regency, Product Innovation does not have an effect on the performance of Furniture SME businesses in Garut Regency and Entrepreneurial Orientation and Product Innovation have a simultaneous effect on the performance of Furniture SME businesses in Garut Regency.